PsychoOncology: a new way to see cancer - Veit, Maria Teresa; de Carvalho, Vicente Augusto (O Mundo da Saúde, 2010)
PsychoOncology, an area of intersection between Psychology and Oncology, studies the psychological and behavioral variables present in the process of sickness and cure and interventions which happen throughout all that process. PsychoOncology has deepened and sharpened techniques for potentiating the effects of medical treatments, enabling each patient to use their mental resources in a focal way, trying to reinforce the effects of medicines they take. It has also developed resources for supporting caretakers, be they professionals or not, so that they act as co-contributors in all stages of treatment, at the same time as it provides strategies for selfcare and strengthening, also with the aim of maintaining their own physical and mental health.